2015
DOI: 10.1097/jto.0000000000000436
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Next-Generation Sequencing of Cancer Genes in Advanced Stage Malignant Pleural Mesothelioma: A Retrospective Study

Abstract: Next-generation sequencing was applied to a relatively large retrospective series of MPM using formalin-fixed, paraffin-embedded archival material. Our results indicate a complex mutational landscape with a higher number of genetic variations in the p53/DNA repair and phosphatidylinositol 3-kinase pathways, some of them with prognostic value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
141
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(159 citation statements)
references
References 26 publications
12
141
2
4
Order By: Relevance
“…A 10% mutation frequency of KDR gene has been reported [8]. Another study reported a frequency of 38/123 patients (30.9%) with mutation in KDR gene in Malignant Pleural Mesothelioma [9]. It is noteworthy to mention here that, a study on non-small cell lung cancer reported high Q472H type of KDR mutation number in 33.3% patients [10] and in another study, it has been suggested to play a role of proto-oncogene in Lung Adeno-carcinoma [11].…”
Section: Discussionmentioning
confidence: 99%
“…A 10% mutation frequency of KDR gene has been reported [8]. Another study reported a frequency of 38/123 patients (30.9%) with mutation in KDR gene in Malignant Pleural Mesothelioma [9]. It is noteworthy to mention here that, a study on non-small cell lung cancer reported high Q472H type of KDR mutation number in 33.3% patients [10] and in another study, it has been suggested to play a role of proto-oncogene in Lung Adeno-carcinoma [11].…”
Section: Discussionmentioning
confidence: 99%
“…However, large deletions of BAP1 have never been detected in germline configuration in families either with multiple MM [3,9,11,[32][33][34][35][36][37] or without MM [26,28,29]. The loss of nuclear BAP1 immunostaining suggests that these tumors may harbor somatic alterations of the BAP1 gene, a frequent event in sporadic epithelial MM [21,24,26,27]. Although most BAP1 somatic mutations are nucleotide-level mutations, additional technical approaches would have been necessary to detect gross deletions at exon level.…”
Section: Discussionmentioning
confidence: 99%
“…The majority are benign polymorphisms (SNPs) or variants of unknown significance (VUS) [4,5,23]. Those of pathogenic significance have been described in association with BAP1-TPDS malignancies [4,21,[24][25][26][27][28]. On the other hand, somatic mutations of BAP1 are a frequent event in MM [26,28,29], with a variable rate of occurrence depending on the molecular assay used.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in genes involved in PI3K signaling have been identified in MPM and are thought to contribute to the pathogenesis of MPM (109). Everolimus inhibits PI3K through binding mTOR and is FDA approved for metastatic breast cancer, renal cell carcinoma, subependymal giant cell astrocytoma, GI and lung neuroendocrine tumors, and for prevention of graft failure (110)(111)(112)(113).…”
Section: Pi3k/akt/mtor Pathway Inhibitorsmentioning
confidence: 99%